Audiences’ Perception of Rape Euphemism In the Sexual Violence News in Online Media - Ade Devia Pradipta; Putu Titah Kawitri Resen (LONTAR: Jurnal Ilmu Komunikasi, 2024)
Online media is a form of mass media that is close to society, especially in the era of increasingly massive development of information and communication technology. One type of information that the public is interested in in online media is news, especially cases of sexual violence such as rape. Rape is a serious crime because it harms the victim from physical and psychological aspects. Reporting about rape incidents generally applies euphemisms for verbs that represent heinous acts. In some cases of rape, the criminal act is replaced with several words such as "digagahi", "dicabuli", "dirudapaksa", even if the perpetrator is more than one person, the word choice used is "digilir". The aim of this research is to describe public perceptions regarding the replacement of the word rape in reporting about sexual violence in online media. The results of this research found that respondents felt that it was important for the media to replace the word rape because it made the news more polite and more comfortable to read. The pronouns most frequently read by respondents were molested and fucked. Furthermore, this research also found that some word choices actually perpetuate the dominance of perpetrators, who are mostly male, over victims, who are usually women or minors.